An exploratory investigation into the self-regulatory processes influencing drug driving: Are young drivers more externally regulated?. (July 2021) - Mills, Laura; Watson-Brown, Natalie; Freeman, James; Truelove, Verity; Davey, Jeremy
Highlights: The first investigation into the self-regulatory processes influencing drug driving. Young drivers were less likely to drug drive than older drivers. Non-drug drivers displayed more internalised regulation than drug drivers. Self-regulation is important to consider in road safety interventions. Abstract: An upward trend in drug driving has been observed in several countries around the world. Research suggests that younger drivers are more likely to engage in drug driving compared to older drivers. There is also evidence to suggest young drivers differ from older drivers in their capacity for self-regulation. Despite this, research has yet to explore the impact of age on the self-regulatory processes with regard to decisions to drug drive among drug users. A total of 507 Queensland drivers (72.8% female), who reported ever taking an illegal drug, were involved in the research. Participants completed an online questionnaire, which collected demographic and drug consumption information, as well as items assessing the self-regulatory processes influencing drug driving, and drug driving behaviour. Regardless of age, participants reported a tendency towards internalised regulation. However, results suggest that young drivers (aged 18–24 years) feel greater belongingness to people who promote safe transport decisions after taking drugs, compared to drivers aged 25 years and over. Interaction effects revealed that for young drug takers, feeling greater relatedness, along with perceiving competence and importance in planning alternative transport after taking drugs, can be protective against drug driving behaviours. Significant predictors of drug driving were lower relatedness, greater perceived pressure to drug drive, lower effort/importance to plan safe alternatives after taking drugs, being of older age, and greater drug abuse. Counterintuitively, perceiving more options (choice) to take alternative transport after taking drugs also predicted the offending behaviour. The results of this study suggest that enhancing drivers' competency to make (and value) safe driving decisions is a critical step for road safety.